The miracle worker : a play for television - Gibson, William, 1914-2008. (New York : Knopf, 1957)
A text of the television play, intended for reading, of Anne Sullivan Macy's attempts to teach her pupil, Helen Keller, to communicate.
Keywords: Keller, Helen, -- 1880-1968 -- Drama; Sullivan, Annie, -- 1866-1936 -- Drama; Drama